An early look at plug-in electric vehicle adoption in disadvantaged communities in California. (June 2019) - Canepa, Kathryn; Hardman, Scott; Tal, Gil
Abstract: Prior research on plug-in electric vehicle (PEV) adoption has revealed that early adopters tend to be wealthy consumers, this may mean that the benefits of PEVs are not being equitably distributed. Extensive research has shown that low-income and minority commutes are disproportionately impacted by environmental and transportation injustice. PEVs can contribute to importing air quality and could provide lower cost and more reliable transportation to low-income and minority communities if they are deployed there. This paper takes an early quantitative look at PEV adoption in disadvantaged communities (DACs), which are census tracts in California that suffer from a combination of economic barriers and environmental burden. We use six datasets to examine PEV market share, socioeconomic characteristics of PEV owners, and PEV charging infrastructure. Analysis confirms that adoption of both new and used PEVs in DACs occurs at very low rates - 5.7% and 8.7% of all PEV sales, respectively - that are disproportionate with the number of households that reside in these areas. Owners of new or used PEVs in DACs have slightly lower incomes than PEV owners in non-disadvantaged communities. However, as a group they have higher incomes, are higher educated, and fewer are home-renters than the DAC average, indicating that they are not representative of their surrounding community. Encouragingly, charging infrastructure is present in DAC census tracts, suggesting that further PEV adoption could be supported. Additionally, there are higher proportions of used PEVs in DACs than new PEVs, which may indicate potential for adoption of these lower-priced vehicles, however rates of adoption are still low. Despite the considerable benefits that PEVs could offer in DACs, there are still substantial barriers to PEV. Key barriers for policy-makers to continually address are the prohibitive price of the technology, lack of knowledge about or ease of accessing PEV incentives, and lack of access to public or private charging infrastructure located near multi-unit housing. Highlights: This paper investigates EV adoption in disadvantaged communities (DACs) in California. Adoption of new or used electric vehicles is lower in DACs than in non-DACs. Some DAC residents do purchase new and used electric vehicles. These buyers are not typical DAC resident though, having high household incomes. More work is needed to increase electric vehicle adoption in DACs.